ByzRev 06.2024.069: Baukje van den Berg, Homer the Rhetorician: Eustathios of Thessalonike on the Composition of the Iliad. Oxford – New York 2022 | Douglas Olson – Eric Cullhed, Eustathius of Thessalonica, Commentary on the Odyssey. II: Rhapsodies 5–8. Leiden: Brill 2023 - Zellmann-Rohrer, Michael (The Byzantine Review, 2024)
Baukje van den Berg, Homer the Rhetorician: Eustathios of Thessalonike on the Composition of the Iliad (Oxford Studies in Byzantium). Oxford – New York: Oxford University Press 2022. xviii + 260 pp. – ISBN 978-0-19-286543-4 Douglas Olson – Eric Cullhed, Eustathius of Thessalonica, Commentary on the Odyssey. Volume II: Commentary on Rhapsodies 5–8. Leiden – Boston: Brill 2023. xxvi + 511 pp. – ISBN 978-9-00-454870-1